Early breastfeeding practices: Descriptive analysis of recent Demographic and Health Surveys. Issue 2 (16th October 2017) - Oakley, Laura; Benova, Lenka; Macleod, David; Lynch, Caroline A.; Campbell, Oona M. R.
Abstract: The aim of this study was to describe early breastfeeding practices (initiation within 1 hr of birth, no prelacteal feeding, and a combination of both—"optimal" early breastfeeding) according to childbirth location in low‐ and middle‐income countries. Using data from the most recent Demographic and Health Survey (2000–2013) for 57 countries, we extracted information on the most recent birth for women aged 15–49 with a live birth in the preceding 24 months. Childbirth setting was self‐reported by location (home or facility) and subtype (home delivery with or without a skilled birth attendant; public or private facility). We produced overall world and four region‐level summary statistics by applying national population adjusted survey weights. Overall, 39% of children were breastfed within 1 hr of birth (region range 31–60%), 49% received no prelacteal feeding (41–65%), and 28% benefited from optimal early breastfeeding (21–46%). In South/Southeast Asia and Sub‐Saharan Africa, early breastfeeding outcomes were more favourable for facility births compared to home births; trends were less consistent in Latin America and Middle East/Europe. Among home deliveries, there was a higher prevalence of positive breastfeeding practices for births with a skilled birth attendant across all regions other than Latin America. For facility births, breastfeeding practices were more favourable among those taking place in the public sector. This study is the most comprehensive assessment to date of early breastfeeding practices by childbirth location. Our results suggest that skilled delivery care—particularly care delivered in public sector facilities—appears positively correlated with favourable breastfeeding practices.